Longitudinal Surveillance and Risk Assessment of Resistance in Escherichia coli to Enrofloxacin from A Large-Scale Chicken Farm in Hebei, China - Kaixuan Guo; Yue Zhao; Luqing Cui; Zhengzheng Cao; Fan Zhang; Xiangru Wang; Zhong Peng; Jiawei Feng; Tianyu Hu; Menghong Dai (MDPI AG, 2021)
The purpose of this study was to investigate the changes of resistance phenotype and plasmid-mediated quinolone resistance genes (PMQRs) in Escherichia coli (E. coli) during enrofloxacin (ENR) administration in different breeding cycles. In 2020, 983 strains of E. coli were isolated from different samples in different cycles at the broiler farm with the largest single batch of slaughter capacity in Hebei Province, China. All samples were from chicken, environmental, and human sources. The sensitivity of the isolates to various antibiotics was determined by broth microdilution method. The findings of this study include: (1) the total isolation rate of E. coli in the four cycles was 63.83% (983/1540); (2) the average resistance rate of E. coli from 1-day-old chickens to enrofloxacin was as high as 75% in each cycle, and with the use of enrofloxacin, the resistance rate of E. coli from chickens gradually increased to 100%; (3) 107 strains of E. coli randomly selected from different cycles and sources demonstrated the multi-drug resistance phenotypes. The highest resistance rate was doxycycline (100%), and the lowest was erythromycin (54.21%); (4) the detection rate of PMQRs of E. coli from chickens in different cycles were always higher than that from environmental and human. In particular, the PMQRs pollution rate of chicken seedlings in each cycle were generally higher than that of other sources; (5) We used SPSS software to analyze the Kendall rank correlation of the experimental data. The resistance of E. coli isolated from this farm to ciprofloxacin (CIP) may increase along with the increase of resistance to enrofloxacin (Kendall's tau-b = 0.190, p = 0.021). All these data highlight the serious problem of bacterial resistance in this farm. Therefore, it is urgent to provide guidance for the prevention and control of colibacillosis and drug resistance in this farm.